Work Discipline as the Key: Moderating the Influence of Training and Workload on Teacher Performance - Widiyanto, Widiyanto; Sutianingsih, Sutianingsih (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study is to determine the influence of teacher training and workload on teacher performance moderated by work discipline within the Coordinator of PAUD Dikdas and LS of Wonosegoro District. The method used in this study is a quantitative method. Quantitative method is defined as research in the form of information or explanations expressed by numbers or numbers which are then analyzed using statistical calculations, from these statistical calculations can describe an object that can be presented in the form of tables or graphs. This study uses the SEM analysis method with the Partial Least Squares (PLS) approach with the help of Smartpls 3.0. Meanwhile, the population in this study is all educators (teachers) within the Coordinator of PAUD Dikdas and LS Wonosegoro District, which is 256 people. This study used a questionnaire. From the tests that have been carried out, the direct test results of teacher training and workload have a positive and significant influence on teacher performance. In the moderation test, work discipline cannot moderate teacher training and workload on teacher performance.